Discovery of Setihercostomus Zhang et Yang in the Afrotropical Region (Diptera: Dolichopodidae) - Grichanov, Igor Ya.; Kaae, Mathias; Pape, Thomas (Zootaxa, 2014)
Setihercostomus Zhang et Yang, 2005 is separated from the genus Hercostomus Loew, 1857, by the following combination of characters: clypeus short and narrow, not reaching lower margin of eyes, bearing one pair of strong bristles in both sexes; pteropleuron (= anepimeron) with group of fine hairs in front of posterior spiracle; male cercus large and thick, nearly as long as epandrium (Zhang & Yang 2005). Prior to this study, the genus has been recorded from the Palaearctic and Oriental regions (Zhang & Yang 2005; Yang et al. 2011), with two species from Oriental China, one known from both Palaearctic and Oriental China, one from Taiwan, and one from the Far East of Russia (Primorskii Territory). A female specimen of Setihercostomus has been recorded from Slovakia (Pollet 2009), which may be conspecific with S. setifacies (Stackelberg 1933) from the Russian Far East.